2018
DOI: 10.1039/c7ra11430c
|View full text |Cite
|
Sign up to set email alerts
|

A novel study on preparation of H2TiO3–lithium adsorbent with titanyl sulfate as titanium source by inorganic precipitation–peptization method

Abstract: A peroxy lithium titanate sol was prepared with low-cost and easily available titanyl sulfate as the titanium source, lithium acetate as the lithium source, and aquae hydrogenii dioxidi as the complexing agent using an inorganic precipitation-peptization method. The sol system was aged, centrifugal-washed, dried and calcined to obtain a pure precursor, Li 2 TiO 3 , followed by pickling with hydrochloric acid to obtain the H 2 TiO 3 -lithium adsorbent. The effects of aging time and calcination temperature on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…A comparison of the XRD patterns of LTO and HTO revealed that the (110) crystal plane were offset, and the (−131) and (−204) crystal planes became wider in HTO due to a change in the bonding modes of Li + and H + ions in the Ti–O layer . The disappearance of peaks corresponding to the (−133) and (−206) crystal planes indicates that Li + ions were successfully extracted from LTO . After doping and coating modifications, the diffraction peak intensity of ion sieve decreased (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the XRD patterns of LTO and HTO revealed that the (110) crystal plane were offset, and the (−131) and (−204) crystal planes became wider in HTO due to a change in the bonding modes of Li + and H + ions in the Ti–O layer . The disappearance of peaks corresponding to the (−133) and (−206) crystal planes indicates that Li + ions were successfully extracted from LTO . After doping and coating modifications, the diffraction peak intensity of ion sieve decreased (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…From the XRD and USAXS/SAXS studies, it is evident that delithiation of β-Li 2 TiO 3 results in significant changes in the crystal structure and morphology. Various authors attributed the missing diffraction peaks after delithiation to the replacement of O–Li ionic bonds in Li 2 TiO 3 with electrostatic interactions of H + ions between HTi 2 layers , (i.e. ; O–H covalent bonds are absent in H 2 TiO 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the adsorption equilibrium was not reached until 24 h. Chitrakar et al prepared the LISs precursor Li 2 TiO 3 from anatase TiO 2 and Li 2 CO 3 , and then eluted with hydrochloric acid to obtain H 2 TiO 3 with a saturated adsorption capacity of 32.6 mg g -1 [22]. Meanwhile, many reported works aimed at improving the adsorption capacity via synthesis method and morphology regulation but ignored the slow adsorption rate [23][24][25].…”
Section: Introductionmentioning
confidence: 99%